GEURAE SEBAGAI PEMARKAH WACANA DALAM PERCAKAPAN BAHASA KOREA - Murtanu, Mellyana; Usmi, Usmi (UI Scholars Hub, 2023)
In Korean, the word geurae is positioned as an exclamation in a sentence. Its use in oral communication has diverse meanings and functions. Previous research shows that, apart from conveying its basic meaning, the word geurae is also often used as a discourse marker (DM), especially in a conversation. DMs are words used by speakers to express their feelings and view about the contents of a conversation to a speech partner. The purpose of this study was to analyze the form, meaning, and function of the word geurae as a DM in Korean conversations. This literature study is linguistics description of gurae, discourse marker. Results show that the word geurae has seven discourse functions that can be categorized into two categories, namely reactive words and progressive words. As a reactive word, it is used to indicate affirmation, surprise, confirmation, and response, whereas as a progressive word, it is used to draw attention and give emphasis.